2016
DOI: 10.1007/s11764-016-0515-x
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle behaviors among US cancer survivors

Abstract: Cancer survivors are at increased risk for comorbid conditions, and acceptance of healthy behaviors may reduce dysfunction and improve long-term health. Ultimately, opportunities exist for clinicians to promote lifestyle changes that may improve the length and quality of life of their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
65
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 15 publications
(30 reference statements)
10
65
4
Order By: Relevance
“…These three studies are all of older date, whereas a recent study by Mowls et al. () has shown similar results as in our study. This could indicate that the policy regulations and mass media campaigns in the last decade emphasising the harmful consequences of tobacco have been successful.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These three studies are all of older date, whereas a recent study by Mowls et al. () has shown similar results as in our study. This could indicate that the policy regulations and mass media campaigns in the last decade emphasising the harmful consequences of tobacco have been successful.…”
Section: Discussionsupporting
confidence: 92%
“…This may be due to the physical limitations individuals with these cancer sites may endure such as having a colostomy, reduced lung capacity and other symptom burdens and poor prognosis that may hinder an active lifestyle. In line with our results, some studies have found that cancer survivors are less likely to be physically active than those with no history of cancer (Kim, Wallington, Makambi, & Adams‐Campbell, ; Mowls et al., ; Wang et al., ), and other studies show no differences between the groups (Berry et al., ; Eakin et al., ; Mayer et al., ), or that cancer survivors are physically more active than the non‐cancer group (Bellizzi et al., ). The way physical activity was measured in the studies varies a lot which could be part of the explanation of these inconclusive results.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations